2022
DOI: 10.3390/insects13020164
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Community-Driven Mosquito Surveillance Program for Vectors of La Crosse Virus to Educate, Inform, and Empower a Community

Abstract: The fields of entomology, geospatial science, and science communication are understaffed in many areas, resulting in poor community awareness and heightened risks of vector-borne diseases. This is especially true in East Tennessee, where La Crosse encephalitis (LACE) causes pediatric illness each year. In response to these problems, we created a community engagement program that includes a yearlong academy for secondary STEM educators in the 6–12 grade classroom. The objectives of this program were to support … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…We aimed to collaborate with educators in east Tennessee to develop a program that would simultaneously increase community awareness of the locally important LACV disease, foster high-impact learning and enthusiasm for students in STEM courses, and produce mosquito surveillance data that would be useful for hypothesis-driven inquiries [ 37 ]. In this study, we found that educators and their students in our program can collect Aedes egg abundance data that closely reflects data collected by our entomology laboratory.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We aimed to collaborate with educators in east Tennessee to develop a program that would simultaneously increase community awareness of the locally important LACV disease, foster high-impact learning and enthusiasm for students in STEM courses, and produce mosquito surveillance data that would be useful for hypothesis-driven inquiries [ 37 ]. In this study, we found that educators and their students in our program can collect Aedes egg abundance data that closely reflects data collected by our entomology laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…In 2019, 17 educators from 13 schools in six different counties participated. In 2020, 15 of those educators from 12 schools in six counties returned to participate in the program’s second year [ 37 ]. In 2021, 13 educators (nine returning and four new) from 12 schools in seven counties participated in the program.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations